Animals in Javanese manuscript illustrations - Meij, Dick van der (Wacana, Journal of the Humanities of Indonesia, 2022)
Most Javanese manuscript illustrations of narrative poems and (pseudo)-historical chronicles (babad) depict only one part of the natural world: animals. Animals are portrayed in relation to the characters in the text they illustrate. Some illustrated Javanese manuscripts are discussed below in relation to the way in which they illustrate the natural world: these are the fictive narrative poems Serat Selarasa, Serat Panji Jayakusuma, Serat Asmarasupi, Serat Jayalengkara Wulang, and Serat Damar Wulan, and the poetic (pseudo)-historical chronicle Babad Perang Demak. It appears from the illustrations in the manuscripts discussed that in the narrative poems the wayang style is preferred and they depict animals differently from the babad for which the wayang-style is not used and whose illustrations tend to be more “realistic”. The focus in the narrative poems discussed here is on serpents, crocodiles, and elephants, and in the babad on all the animals featured.